The Relationship Between Entrepreneurial Spirits and Entrepreneurial Value in Improving Business Self-Reliance: A Proposed Model - Yusi, Syahirman (Jurnal Riset Bisnis dan Investasi, 2022)
Small and medium enterprises (SMEs) had an important role in the national economy, as the social economy, the SMEs played a role in absorbing employment, economic service, equity process, increasing income, economic growth, and national stability. Although in practice the development efforts have been carried out, in reality, these SMEs had not been fully free from problems or constraints faced. The objective of this study was to find out the relationship between entrepreneurial spirit, entrepreneurial value and business self-reliance. Primary data were obtained through answers to questionnaires from 250 respondents who were randomly assigned and processed through Structural Equation Modeling (SEM) analysis. The conclusion obtained was both entrepreneurial spirit and entrepreneurial value directly had positive effects on the business self-reliance. Through variables in the form of entrepreneurial behaviour, entrepreneurial spirit and entrepreneurial value also influenced positively. The results of the analysis provided explanations that all research hypotheses were acceptable.